KONVERGENSI DAN DIGITALISASI MEDIA: TANTANGAN INDUSTRI MEDIA (Konvergensi Media MNC Grup dan Kompas Gramedia di Indonesia) - Nanik Mujiati (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mmojokerto, 2022)
The development of information technology and communication requires the media industry to adapt to new media presence. New media has created a convergence process between digital technology and network interconnectivity. This article focuses on how a media industry deals with the challenges of convergence and digitalization. Among other features of the new media’s convergence and digitalization of the media is the MNC Group and Kompas Group (Gramedia’s Kompas) in Indonesia. The MNC group and the Kompas group seek to optimize the media to be distributed to the masses or the viewers. It is necessary to organize production in multiplatforms. This article, underlies a study of how media convergence affected the production of these two media industries. Keywords: Convergence, Digitalization, Media Industry